Effect of chemical structure and cross-link density on the heat resistance of phenolic resin. (January 2015) - Wang, Yong; Wang, Shujuan; Bian, Cheng; Zhong, Yuhu; Jing, Xinli
Abstract: Limited by the knowledge of the structure and pyrolysis mechanism of cured phenolic resin (PR), the influence of cross-link density (CLD) on the heat resistance of PR remains unclear. The objective of this work is to characterize the structure of PR and understand the relationship between structure and heat resistance. The CLD of cured PR is characterized by theoretical and experimental approaches based on the full understanding of the chemical structure. The influence of CLD on the heat resistance is studied by analyzing the pyrolysis behavior of cured PR, and the results reveal that cross-link can improve the thermal stability and char yield of cured PR simultaneously. A novel pyrolysis mechanism and a quantitative relationship between the CLD and residual weight of PR are proposed. The results of our paper provide a theoretical basis to develop resins with good heat resistance.